Implementasi Pembelajaran Manajemen Pendidikan Islam dalam Membentuk Kompetensi Manajerial Mahasiswa Manajemen Pendidikan Islam - Akhmed Reza Fachlevi; Bahrani; Sudadi (STKIP Subang, 2026)
This study aims to describe the implementation of Islamic Education Management learning in shaping the managerial competencies of students in the Islamic Education Management study program, covering planning, organizing, actuating, and controlling functions. This research employed a descriptive qualitative approach. The subjects were 25 fifth-semester students who had completed core courses in Islamic Education Management. Data were collected through classroom observations, semi-structured interviews with students and lecturers, and documentation of learning devices. Data analysis followed the Miles and Huberman model, with source and method triangulation used to ensure data validity. The findings revealed three main points. First, the current design of Islamic Education Management learning is dominated by interactive lectures (30%), case discussions (30%), and field project assignments (40%). Second, the most effective methods for developing students' managerial competencies were project-based learning and real-case studies from Islamic educational institutions. Third, the main obstacles included limited access to field simulations, a lack of lecturers with practitioner backgrounds in management, and the still-normative integration of Islamic values into each management function. This study offers a new perspective on the necessity of reconstructing Islamic Education Management learning from a theoretical approach toward a contextual-collaborative one, emphasizing the development of managerial competencies grounded in Islamic ethics.